Public health leadership in a VUCA world environment: lessons learned during the regional emergency rollout of SARS-CoV-2 vaccinations in Heidelberg, Germany, during the COVID-19 pandemic - Schulze, Christoph; Welker, Andreas; Kühn, Anne; Schwertz, Rainer; Otto, Benjamin; Moraldo, Laura; Dentz, Udo; Arends, Albertus; Welk, Eckhard; Wendorff, Jean-Jacques; Koller, Hans; Kuss, Doreen; et al. (Vaccines, 2021)
The purpose of this work is to share methods used and lessons learned during a comprehensive inter-institutional pandemic disaster response in Heidelberg, Germany, conveying experiences of the regional SARS-CoV-2 vaccination rollout campaign for up to 1,000,000 vaccines in the year 2020. In this volatile, uncertain, complex, and ambiguous (VUCA) environment, the following five strategic elements were pertinent for institutional arrangements so that specific contributions of the various project partners would be available fast without the necessity of extensive negotiations or information exchange: (1) robust mandate, (2) use of established networks, (3) fast onboarding and securing of commitment of project partners, (4) informed planning of supply capacity, and (5) securing the availability of critical items. Planning tools included analyses through a VUCA lens, analyses of stakeholders and their management, possible failures, and management of main risks including mitigation strategies. The method of the present analysis (VUCA factors combined with analyses of possible failures, and management of stakeholders and risks) can theoretically be adjusted to any public health care emergency anywhere across the globe. Lessons learned include ten tactical leadership priorities and ten major pitfalls.